aplikasi Penerapan Aspek Green Building pada Rumah Tinggal Masyarakat - Jeumpa, Kemala; Harahap, Rumilla (Universitas Islam Negeri Sunan Ampel Surabaya, 2023)
This paper delves into the application of green building aspects in historical and modern homes, driven by the imperative to address the environmental impacts of building construction. Against the backdrop of evolving human needs and architectural forms, the study aims to assess the extent of green building implementation in typical old and modern houses. Methodologically, the research conducts a comprehensive analysis of six key aspects of green building—Appropriate Site Development, Energy Efficiency and Conservation, Water Conservation, Material Resources and Cycle, Indoor Health and Comfort, and Building Environment Management—through random observations of representative buildings from different time periods. The results indicate a notable discrepancy in the adoption of green aspects between historical and modern homes, with historical houses exhibiting a higher degree of integration. Specifically, historical homes scored 41 points in green aspect implementation, while modern houses scored 22 points. These findings underscore the importance of prioritizing sustainable building practices to mitigate environmental impacts and promote holistic well-being in residential constructions.